Unraveling the Mysteries of the Cosmos: A Comprehensive Review of Dark Matter and Dark Energy Theories - Youseff, Kumar Kukku (Journal of Educational Research and Policies, 2026)
The composition of our universe presents one of the most profound enigmas in modern cosmology. Current evidence suggests that ordinary baryonic matter—the substance of stars, planets, and all visible cosmic structures—constitutes a mere 5% of the universe's total content. The remaining 95% comprises two elusive components: dark matter (~27%) and dark energy (~68%). Despite their dominance in cosmic composition, these "dark" components remain largely mysterious, detectable primarily through their gravitational effects. This comprehensive review synthesizes contemporary understanding of dark matter and dark energy, examining observational evidence, theoretical frameworks, and the intricate relationship between these cosmic components. By analyzing galactic rotation curves, gravitational lensing, cosmic microwave background measurements, and large-scale structure formation, we illuminate the compelling case for dark matter's existence. Similarly, we evaluate evidence for dark energy through type Ia supernovae observations, baryon acoustic oscillations, and cosmic expansion measurements. The review concludes by addressing unresolved questions, ongoing experimental efforts, and future research directions aimed at illuminating these cosmic shadows that shape our universe's past, present, and future evolution.